(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Taking into consideration the ethnic composition, Singapore and Macedonia are defined as multiethnic societies. According to the composition and the size of the population in both countries, there are: one large ethnic community (the Chinese in Singapore and the Macedonians in Macedonia) and the other non- majority communities (in the case of Singapore, the Malaysian and Indian communities, as well as other smaller communities included in the group of "Others ", while in the Macedonian case, it is the Albanian community, which is the most numerous of the non-majority and the Turkish, Serbian, Roma, Vlach and Bosniak non-majority communities). Based on civic principle both countries do not neglect the multicultural character of the population and promote policies for its consolidation. This paper aims, by comparing constitutional provisions and the policies for identity building and policies for promotion of multiculturalism of the both cases, to check what are the differences or similarities between Singaporean and Macedonian case and what Macedonia can learn from the Singapore example.